Cardiovascular and metabolic risk factors of shift workers within the automotive industry - Andre L. Travill (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2019)
Background: Previous research highlighted the importance of identifying the modifiable risk factors among shift workers in specific industries to take effective preventative and therapeutic steps to decrease the risks associated with non-communicable chronic diseases. Aim: The aim of this study was to investigate the prevalence of cardiovascular and metabolic disease risk factors among shift workers within the automotive industry. Setting: This study was conducted at a car manufacturing company in the Eastern Cape Province of South Africa. Methods: The study employed a cross-sectional quantitative design. Body mass index was calculated, and the American College for Sports Medicine classification for normal weight, overweight and obesity was used to assess the weight status of the workers. Fasting blood glucose and cholesterol as well as blood pressure (BP) were also measured. Results: Seventy-five automotive shift workers participated in the research. Twenty-three per cent of the participants had no risk factors, 30.6% had one risk factor, 34.7% had two risk factors and only 5.3% exhibited four risk factors. Sixty-six percent of participants were classified as either pre-obese or obese, while 55% were hypertensive. Systolic BP (r = 0.258; p 0.05), diastolic BP (r = 0.342; p 0.01), cholesterol (r = 0.258; p 0.05) and age (r = 0.271; p 0.05) significantly correlated with body mass index. Conclusion: This study highlights the prevalence of risk factors for cardiovascular diseases among employees in the automotive industry. However, it does not show any risk factors for metabolic diseases.